Physiochemical, Mechanical and Antibacterial Properties of Sodium Alginate/Copper Oxide BioComposite Film for Wound Healing Applications - JAMAL, IYLIA IZZATI; IDRIS, MAIZLINDA IZWANA (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The objectives of this study are to fabricate alginate and copper oxide biocomposite film via solution casting method. At the earlier stage, the alginate solution with 1wt% was prepared and later mix with the 0.5, 1.0and 1.5 gram of copper oxide. The combination of alginate and copper oxide was stirred for 3 minutes before proceeding to casting process and left for 24 hours. When the films are ready, it was crosslinked with calcium chloride. The biocomposite film was dried in the room temperature for 24 hours. Then, the fabricated film was characterised and analysed by using Fourier Transform Infrared Spectroscopy (FTIR) and contact measurement, thickness analysis and viscosity analysis also being conducted in order to study the characterization of the film. Also the antibacterial assessment was carried out by using disc diffusion method (Kirby-Bauer test).